Noise Analysis, Lighting, Work Climate, Mechanical Vibration, Work Tenure and Nutritional Status Towards Fatigue (Universitas Negeri Semarang, 2020)
Work fatigue is an important problem that needs to be dealt with properly because it can cause a loss of efficiency at work, decreased productivity and work capacity as well as health and survival skills that cause workplace accidents. This study was aimed to analyze the factors that influence fatigue. Observational analytic research design with cross sectional approach was used with simple random sampling. The data collection techniques used observation and interviews. The sample of research was in the weaving department were 60 workers. The variables studied were noise, lighting, work climate, vibration, work tenure and nutritional status. Based on Fisher's Exact Test analysis, there is no relationship between noise and fatigue p= 0.611 Î± = 0.05. There is no relationship between lighting with fatigue p= 0.392 Î± = 0.05. There is no relationship between work climate with fatigue p= 0.608 Î±= 0.05. There is no relationship between mechanical vibration with fatigue p = 0.199 Î±= 0. There is no relationship between work tenure with fatigue p= 0.309 Î±= 0.05. There is no relationship between nutritional status with fatigue p = 0.475 Î± = 0.05. The conclusion of this study is that there is no significant relationship between noise (p= 0.611), lighting (p= 0.392), climate (p= 0.608), vibration (p = 0.199), work tenure (p= 0.309), and nutritional status (p= 0.475) with work fatigue. For the further study, it is recommended to add other variables such as work shifts, sleep duration, financial conditions and a larger sample size.